Asas Kemanfaatan Dan Asas Keadilan Dalam Penetapan Upah Minimum - Sari, Destya Permata; Subekti, Rahayu (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2023)
The research in this article aims to find out whether the mechanism implemented in determining the minimum wage for the City of Surakarta in 2022 is or is not in accordance with Government Regulation Number 36 of 2021 concerning Wages, and to analyze whether or not the decision of the minimum wage for the City of Surakarta in 2022 has fulfilled the principles of expendiency and fairness for workers and employers. This research uses a type of empirical legal research with a descriptive nature, then the data is analyzed qualitatively. The study shows the results that the mechanism for determining the minimum wage for the city of Surakarta in 2022 is normatively not fully in accordance with Government Regulation Number 36 of 2021 concerning Wages. In addition, the decision of the Surakarta Minimum Wage for 2022 has not been able to fulfill the principles of expendiency and fairness for workers and employers, due to significant changes in the mechanism for setting the city's minimum wage for 2022 and the role of workers and employers in the city minimum wage setting process is still strictly limited by applicable regulations.